Estudio de prefactibilidad para la fabricación de cremas hidratantes corporales a base de açaí y aceite de jojoba - Vidal Llontop, Bertha Grimanesa (2020)
The following research project aims to determine the technical, social, economic and financial viability of installing a anufacturing plant for body hydrating cream based on acai and jojoba oil. The product, whose brand name will be Ecocream, will come in a 150 ml glass bottle and will be distributed to the channels in boxes of 24 containers. This will be sold in the supermarkets and pharmacies of Metropolitan Lima to cover the demand of men and women aged 18-65 years of socioeconomic levels A / B and C. After having projected the demand based on the historical consumption of body creams in Peru and having applied the correction factors as a result of the survey and the segmentation, it was estimated that the demand for 2026 will be 165,493 bottles. The production plant will be located in Lurín, district of the department of Lima. Likewise, it was determined that the project will be limited by the market, because according to the size of the technology, up to 197,494 bottles can be produced. The production process will be semi-automatic. In general, between administrative and plant employees, there will be 17 people. To implement the project, a total investment of S/ 631,594 will be required, which will be financed 35% with a TEA of 12.50%. For the life horizon of the project, which is equivalent to 6 years, a VAN and Economic TIR of S/ 1,458,929 and 73.78% respectively were estimated. On the financial side, there is a VAN of S/ 1,459,513 and TIR of 88.01%. In addition, it will generate a positive impact on society. This is reflected in the value added indicator of the project, which is equivalent to S / 7,418,573.